Peran Pemerintah Daerah dalam Meningkatkan Pelayanan Publik Melalui Inovasi Digital di Kabupaten Pandeglang - Ari Supriadi; Hayati Hayati; Rina Dwi Anggaraeni; Rini Rahmawati (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2026)
The rapid development of digital technology has encouraged local governments to reform public service delivery in order to become more effective, transparent, and responsive to community needs. Pandeglang Regency, as a region that is gradually implementing digital-based public service innovations, faces both challenges and opportunities in this transformation process. This study aims to analyze the role of local government in improving public services through digital innovation in Pandeglang Regency by examining the forms of innovation implemented, the implementation process, and the perceived impacts on the community. This research employed a qualitative descriptive approach, with data collected through in-depth interviews, observations, and document analysis. The findings indicate that the local government plays a crucial role in promoting digital innovation through policy formulation, institutional coordination, and the provision of supporting resources. The implementation of digital innovation has contributed to improved service efficiency, increased access to information, and enhanced service transparency. However, the effectiveness of these innovations remains uneven due to limitations in human resource capacity and varying levels of digital literacy among citizens. The implications of this study suggest that successful digital innovation in public services requires sustained commitment from local governments, continuous capacity building for public officials, and inclusive service strategies to ensure that the benefits of digital transformation are equitably experienced across different segments of society.